Respuesta :
[tex](x^2-1)^2-11(x^2-1)+24=0[/tex]
Use substitution: [tex]x^2-1=t[/tex]
[tex]t^2-11t+24=0\\\\t^2-8t-3t+24=0\\\\t(t-8)-3(t-8)=0\\\\(t-8)(t-3)=0\iff t-8=0\ \vee\ t-3=0\\\\t=8\ \vee\ t=3[/tex]
we're going back to substitution:
[tex]x^2-1=8\ \vee\ x^2-1=3\ \ \ \ |add\ 1\ to\ both\ sides\ of\ the\ equations\\\\x^2=9\ \vee\ x^2=4[/tex]
therefore
[tex]x=\pm\sqrt9\ \vee\ x=\pm\sqrt4\\\\\boxed{x=-3\ \vee\ x=3\ \vee\ x=-2\ \vee\ x=2}[/tex]
Use substitution: [tex]x^2-1=t[/tex]
[tex]t^2-11t+24=0\\\\t^2-8t-3t+24=0\\\\t(t-8)-3(t-8)=0\\\\(t-8)(t-3)=0\iff t-8=0\ \vee\ t-3=0\\\\t=8\ \vee\ t=3[/tex]
we're going back to substitution:
[tex]x^2-1=8\ \vee\ x^2-1=3\ \ \ \ |add\ 1\ to\ both\ sides\ of\ the\ equations\\\\x^2=9\ \vee\ x^2=4[/tex]
therefore
[tex]x=\pm\sqrt9\ \vee\ x=\pm\sqrt4\\\\\boxed{x=-3\ \vee\ x=3\ \vee\ x=-2\ \vee\ x=2}[/tex]
Answer:
x = ± 3 and ± 2
Step-by-step explanation:
The given quadratic equation is
[tex](x^{2}-1)^{2}-11(x^{2}-1)+24=0[/tex]
To make this question easier we will consume ( x² -1 ) = a
a² - 11a + 24 = 0
Now we can factorize this equation easily
a²- 8a - 3a + 24 = 0
a (a-8) - 3 ( a-8) = 0
( a-3 ) ( a-8 ) = 0
Therefore, a - 3 = 0 ⇒ a = 3
or a - 8 = 0 ⇒ a = 8
Now we put the value a
when a = 3 (x² - 1) = 3
x² = 3 + 1 = 4
x = √4
= ± 2
when a = 8 (x² - 1) = 8
x² = 9
x = √9
= ± 3
Therefore, x = ± 3 and ± 2 will be the answer.